ANALYSIS OF TEACHERS' OBSTACLES IN THE IMPLEMENTATION OF THE INDEPENDENT LEARNING CURRICULUM AT SD NEGERI 2 MEUREUDU PIDIE JAYA - Shavira, Nadia; Yamin, M.; Nurmasyitah, Nurmasyitah (Elementary Education Research, 2025)
Renewing the education curriculum needs to be carried out in order to improve the quality of education in Indonesia and create quality Human Resources (HR) that are able to compete with other countries in line with current developments. The independent learning curriculum is a policy that has been designed by the government with the aim of achieving significant progress in terms of the quality of education, thereby producing students and graduates who are ready to face complex future challenges. This curriculum has only been implemented in the 2021/2022 school year, and not all schools have implemented it. Therefore, there are still limited references regarding the independent learning curriculum, especially at the basic education level. The formulation of the problem in this research is "what are the obstacles for teachers in implementing the independent curriculum at SD Negeri 2 Meureudu Pidie Jaya?". This research aims to determine the obstacles teachers face in implementing the independent curriculum at SD Negeri 2 Meureudu Pidie Jaya. The approach in this research is a qualitative approach, the type of research is descriptive. The research subjects were class I, II, IV and V teachers at SD Negeri 2 Meureudu Pidie Jaya. Data collection techniques use observation and interviews, while data analysis techniques use data reduction, data presentation and drawing conclusions. The research results obtained can be concluded that the obstacles most often faced by teachers in implementing the independent learning curriculum are: a) Very many administrative demands; b) Teachers who do not yet have broad insight regarding the independent curriculum; c) Teachers who often do not master the use of technology; d) Teachers who have difficulty identifying differences in students' backgrounds and characteristics; and e) Students who also find it difficult to adapt from the previous curriculum they underwent.